The search of the geotouristic heritage in the Colombian llanos Foothills and adjacent plains: implications for the origin of the current landscape - Germán Chicangana (Boletín de Ciencias de la Tierra, 2020)
In the Colombian Llanos Foothills Department of Meta, five places were chosen to endorse its geology for Geotourism purposes by the Universidad Santo Tomás sede Villavicencio, From the data collected in the field, secondary geologic information verified was possible define a evolution model of the landscape related to the Llanos Foothills and adjacent plains from a geotectonic point of view, giving with this the importance of a role in the Colombian geological heritage for the understanding of the recent geological evolution (Miocene - Holocene) of this sector of Colombian territory. The geological evolution have a long history of the conformation of the crust which covers from the Mesoproterozoic to the Present, and the landscape evolution, both the Piedmont which is part of the Eastern Cordillera, like the Colombian eastern plains were formed from the Upper Miocene to the Present.